Interdependence of attachment styles and relationship quality in parent-adolescent dyads. (December 2017) - Chow, Chong Man; Hart, Ellen; Ellis, Lillian; Tan, Cin Cin
Abstract: The current study examined how attachment styles of parents and adolescents may jointly influence the quality of their relationship. Parent-adolescent ( N dyads  = 77) pairs were recruited from a Midwestern town in the United States. The mean of adolescents' age was 16.25. Both members reported their attachment styles, relationship closeness, and relationship discord. The Actor-Partner Interdependence Model (APIM) showed that both members' attachment avoidance was associated with self-report lower levels of closeness. Parents' attachment anxiety was related to relationship discord. Parents with higher avoidant attachment reported lower closeness when adolescents were higher in avoidant attachment. Higher parents' anxious attachment was related to higher relationship closeness when adolescents were higher on anxious attachment. Such an association was negative when adolescents had lower anxious attachment. Higher parents' anxious attachment was related to greater discord when adolescents were lower on anxiety attachment. This study reveals the complex dyadic dynamics of relationship quality in parent-adolescent pairs.